Postsynaptic Y654 dephosphorylation of β‐catenin modulates presynaptic vesicle turnover through increased n‐cadherin‐mediated transsynaptic signaling. Issue 1 (8th July 2016) - Chen, Chin‐Yi; Chen, Yi‐Ting; Wang, Jen‐Yeu; Huang, Yi‐Shuian; Tai, Chin‐Yin
ABSTRACT: Synaptic adhesion molecules, which coordinately control structural and functional changes at both sides of synapses, are important for synaptogenesis and synaptic plasticity. Because they physically form homophilic or heterophilic adhesions across synaptic junctions, these molecules can initiate transsynaptic communication in both anterograde and retrograde directions. Using optical imaging approaches, we investigated whether an increase in postsynaptic N‐cadherin could correspondingly alter the function of connected presynaptic terminals. Postsynaptic expression of β‐catenin Y654F, a phosphorylation‐defective form with enhanced binding to N‐cadherin, is sufficient to increase postsynaptic surface levels of N‐cadherin and consequently promote presynaptic reorganizations. Such reorganizations include increases in the densities of the synaptic vesicle protein, Synaptotagmin 1 and the active zone scaffold protein, Bassoon, the number of active boutons and the size of the total recycling vesicle pool. In contrast, synaptic vesicle turnover is significantly impaired, preventing the exchange of synaptic vesicles with adjacent boutons. Together, N‐cadherin‐mediated retrograde signaling, governed by phosphoregulation of postsynaptic β‐catenin Y654, coordinately modulates presynaptic vesicle dynamics to enhance synaptic communication in mature neurons. © 2016 Wiley Periodicals, Inc. Develop Neurobiol 77: 61–74, 2017